Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM